Diabetes Melitus Tipe 2 dan Hipertensi sebagai Faktor Risiko PJK pada Lansia - Maulina, Nora; Sawitri, Harvina; Zakiyya, Najwa; Syifa, Siti (FAKULTAS ILMU KESEHATAN UNIVERSITAS MUHAMMADIYAH PAREPARE, 2023)
The elderly are still a significant concern today, because of the many types of diseases that this group suffers from, including coronary heart disease. This disease often coincides in the elderly due to changes in the characteristics of the elderly blood vessels coupled with uncontrolled diet and physical activity, therefore it is important to conduct research related to the relationship between type 2 diabetes mellitus and hypertension in the elderly as a risk of heart disease so that education can be carried out to prevent an increase in the incidence of coronary heart disease. The purpose of this study was to analyze the risk factors for type 2 diabetes mellitus and the incidence of hypertension as a risk factor for coronary heart disease (CHD) using a Framingham risk score for the elderly at the nursing home at Lhokseumawe City in 2022. The research design used was a cross-sectional study in which exposure and impact are measured at the same time. The sample is all the elderly in the nursing home in Lhokseumawe City. The results showed a significant relationship between diabetes mellitus and hypertension on the risk of coronary heart disease. In conclusion, diabetes mellitus and hypertension are risk factors for coronary heart disease.